Production and characterization of alginate-starch-chitosan microparticles containing stigmasterol through the external ionic gelation technique - Gislene Mari Fujiwara; Ranieri Campos; Camila Klocker Costa; Josiane de Fátima Gaspari Dias; Obdulio Gomes Miguel; Marilis Dallarmi Miguel; Francisco de Assis Marques; Sandra Maria Warumby Zanin (Universidade de São Paulo, 2013)
Stigmasterol - a plant sterol with several pharmacological activities - is susceptible to oxidation when exposed to air, a process enhanced by heat and humidity. In this context, microencapsulation is a way of preventing oxidation, allowing stigmasterol to be incorporated into various pharmaceutical forms while increasing its absorption. Microparticles were obtained using a blend of polymers of sodium alginate, starch and chitosan as the coating material through a one-stage process using the external gelation technique. Resultant microparticles were spherical, averaging 1.4 mm in size. Encapsulation efficiency was 90.42% and method yield 94.87%. The amount of stigmasterol in the oil recovered from microparticles was 9.97 mg/g. This technique proved feasible for the microencapsulation of stigmasterol.